Culavedalla Sutta, or, Discourse on various aspects of Buddha's dhamma - Sobhana, Mahā caññʻ Cha rā toʻ ʼA rhaṅʻ, 1904-1982 (Veda Sarpay, 1981)
On a Buddhist sermon from Majjhimanikāya, canonical text.